2007
DOI: 10.1109/tbme.2006.883732
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated System for Multichannel Neuronal Recording With Spike/LFP Separation, Integrated A/D Conversion and Threshold Detection

Abstract: Abstract-A mixed-signal front-end processor for multichannel neuronal recording is described. It receives twelve differential-input channels of implanted recording electrodes. A programmable cutoff HPF blocks DC and low frequency input drift at about 1Hz. The signals are band-split at about 200Hz to low-frequency local field potential (LFP) and high-frequency spike data (SPK), which is band limited by a programmablecutoff LPF, in a range of 8-13kHz. Amplifier offsets are compensated by 5-bit calibration DACs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…16 A versatile VLSI system which can interface to all these modalities is highly desirable. Several VLSI systems have been developed previously [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] to acquire different neural signals. Typically the range of frequencies covered by any one of these systems is limited to one or two signal modalities, to accommodate high efficiency for the targeted application.…”
Section: Neuropotential Interfacementioning
confidence: 99%
“…16 A versatile VLSI system which can interface to all these modalities is highly desirable. Several VLSI systems have been developed previously [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] to acquire different neural signals. Typically the range of frequencies covered by any one of these systems is limited to one or two signal modalities, to accommodate high efficiency for the targeted application.…”
Section: Neuropotential Interfacementioning
confidence: 99%
“…The low noise figure was achieved using chopper stabilization technique and external components. Recently, Perelman et al [17] showed on-chip amplification and separation of spikes from LFPs. The amplifier draws 75 µA from the supply for an input-referred noise of 3 µV.…”
Section: Introductionmentioning
confidence: 99%
“…New technologies have been developed in order to overcome the experimental difficulties which limit the number of neurons studied at the same time, the temporal constraints due to the placement of the electrodes and the mechanical damage of the cells during the functional study. In this context, MicroElectrode Arrays (MEA) have been designed [6]. Planar MEA, like electrodes matrixes, have been spread for the first time in the 1970s.…”
Section: Introductionmentioning
confidence: 99%